Coverage of the Vaso de Leche and Qali Warma programs among children under five years of age and their associated factors - Cherres Bernal, Ana Lucía (2024)
Objective: To estimate the coverage of being a beneficiary of the Vaso de Leche (VDL – Glass of Milk) and Qali Warma (QW – Vigorous Child) programs among children under 5 years of age and to determine the associated factors. Materials and methods: This study used a secondary source, based on the 2022 Encuesta Demogrática y de Salud Familiar (Endes – National Demographic and Family Health Survey) in Peru. For this purpose, women aged 15 to 49 years with children aged five years or younger and complete anthropometric data were selected to answer questions about being a beneficiary of the VDL and QW programs. The dependent variable was being or not a beneficiary of the programs, and the rate of beneficiaries was compared across levels of the independent variables. A log-binomial regression from the family of generalized linear models was used for the multivariate analysis, with a significance level of 5 %. Results: Among children under five years of age, the rate of beneficiaries of the VDL program was 34.13 %, while that of the QW program was 85.88 %. Variables associated with being a beneficiary of the VDL program included being ≥ 12 months, birth weight < 2,500 g, mother’s level of education, belonging to the poorest quintiles and rural residence. The factors associated with being a beneficiary of the QW program included rural residence and belonging to the poor and poorest quintiles. There was no association between being a beneficiary of the QW (aPR: 1.01; 95 % CI: 0.97-1.05) and VDL (aPR: 1.02; 95 % CI: 0.97-1.07) programs and being a child with chronic malnutrition at the time of the survey. Conclusions: The coverage of the VDL and QW programs differs significantly and varies according to sector. Being from the poorest quintile and living in rural areas were common correlates across both programs. Nevertheless, these programs also benefited children who were not necessarily in socioeconomically disadvantaged conditions, suggesting issues in the implementation of the intended objectives.